Gulo gulo Pallas 1780 - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2009)
8. Wolverine Gulo gulo French: Carcajou / German: Vielfrafls / Spanish: Gloton Taxonomy. Mustela gulo Linnaeus, 1758, Lapland. Two subspecies are recognized. Subspecies and Distribution. G. g. gulo Linnaeus, 1758 — NE & NW China, Mongolia, Russia, and Scandinavia. G. g. luscus Linnaeus, 1758 — Canada and W USA (Alaska, California, Idaho, Oregon, Montana, Washington & Wyoming). Descriptive notes. Head-body 65-105 cm, tail 21-26 cm; weight 11-18 kg (males), 6-12 kg (females), adult males are larger and heavier than females. The Wolverine is heavily built and stocky, and is the largest terrestrial member of the Mustelidae. The pelage is long and varies in color from almost blond to dark brown, with two distinctive yellowish stripes that run from the top of the neck to the rump. White patches on the throat, belly or limbs are common. The head is large, with a broad forehead, broad nose, and rounded ears. The limbs are relatively short and the tail is bushy. The feet are large, with well-developed claws. The skull is exceptionally robust and broad, with a well-developed sagittal crest. Dental formula: 13/3, C 1/1, P 4/4, M 1/2 = 38. The teeth are big and strong; the carnassials are very large. Habitat. Wolverines are found in mature conifer forests in the taiga and in the treeless tundra. They are inhabitants of remote northern areas where there are few humans. Wolverines make greater use of forested areas during winter, and greater use of tundra during summer. Altitudinal movements may also occur seasonally, with higher elevations being occupied during the summer and lower altitudes during the winter, probably because of snow accumulation and prey abundance. In central Idaho, USA, radiotracked Wolverines used higher elevations in summer versus winter, and they shifted use of cover types from whitebark pine (Pinus albicaulis) in summer to lower elevation Douglas-fir (Pseudotsuga menziezii) and lodgepole pine (Pinus contorta) communities in winter. Wolverines also preferred northerly aspects, but avoided roads ...